Preparation of aldehyde-graphene quantum dots from glucose for controlled release of anticancer drug - Shi, Shih-Chen; Liu, Hsin-Hung; Chen, Tao-Hsing; Chen, Chih-Kuang; Ko, Bao-Tsan (Frontiers in Materials, 2023)
In this study, we prepared graphene quantum dots (GQDs) via a green process using rice straw as a carbon source. The non-toxic nature of GQDs is suitable for application in human body-related research. Furthermore, GQDs possess biodegradability and biocompatibility characteristics, indicating high suitability for applications in the field of drug delivery. Based on the fact that acid-sensitive bonds between GQDs and the drug doxorubicin are formed by aldehyde groups on GQD surfaces, we adopted a semi-modified TEMPO method to partially oxidize the surface functional groups of GQDs without destroying the structure. This enabled an increase in the surface aldehyde group content, which in turn enhanced the drug loading capacity of GQDs. The aldehyde group content of the GQDs was measured via Fourier transform infrared (FTIR) spectroscopy, titration based on the Cannizzaro reaction, and X-ray photoelectron spectroscopy (XPS). The drug loading effect of the GQDs was determined via absorbance measurements at 485 nm on a UV–Vis spectrophotometer. The results indicated that the semi-modified TEMPO method significantly affected the introduction of surface aldehyde groups and the enhancement of the drug loading efficiency in GQDs. Finally, the polymeric material cationic poly(vinylcyclohexene carbonates) (CPVCHCs) was used for the encapsulation of GQDs and regulation of drug release. Under the premise that the total amount of drugs released remains unaffected, the initial burst release of the drug is effectively delayed, which aids in reducing harmful effects of the drug on the human body.